Women and Minority Film Directors in Hollywood: Performance Implications of Product Development and Distribution Biases. (February 2023) - Karniouchina, Ekaterina V.; Carson, Stephen J.; Theokary, Carol; Rice, Lorien; Reilly, Siobhan
With representation issues in Hollywood coming under intense scrutiny, the movie industry is wrestling with gender- and race-related imbalances in its power structure. One area of concern is the small proportion of women and people of color retained as film directors, coupled with little evidence of improvement in representation among widely released U.S. movies over time. In this study, the authors examine factors that explain gender- and race-related performance disparities in the movie industry. They estimate a two-stage model that accounts for the effects of selection in matching director gender and race to (1) projects of varying potential, (2) production budgets, and (3) the number of screens secured during distribution. They use instrumental variables for revenue, budget, screens, and audience reviews and find that once endogeneity and selection are captured by the models, gender- and race-based performance differences disappear. The results show evidence of biases favoring male, nonminority directors in project assignment, budgeting, and distribution. These biases are stronger for movies with female and minority lead actors but weaker for directors with high clout and for international directors. A matched-sample analysis illustrates that women directors produce similar outcomes with lower budgets and that minority directors produce outsized revenues with equivalent budgets.